FACTORS ASSOCIATED WITH PATIENTS’ ADHERENCE TO SELF-CARE BEHAVIORS AMONG PATIENTS WITH DIABETES MELLITUS: A LITERATURE REVIEW: LITERATURE REVIEW - Gabby Novikadarti Rahmah; Tintin Sukartini; Sri Utami (International Journal of Nursing and Health Services (IJNHS), 2019)
Diabetes Mellitus is a major public health problem. Adherence to self-care behaviors become one of the factors on diabetes severity. This literature review aimed to identify factors associated with ptients’ adherence to mself-care behaviors among patients with type 2 diabetes mellitus. Articles reviewed in this study were searched using several databases including SCOPUS, EBSCO, Science Direct, SAGE, and CINAHL. Keywords used were “Adherence”, "Diabetes Mellitus", "Self-Care", and "Qualitative Research". The results found that several factors indicated as the major of self-care adherence as follows: 1) prominent supporting factor including financial support, and emotional support; and 2) inhibiting support such as patients’ understanding, individual preference, patient's conception, and social and cultural activities. The findings are important sources to formulate the suitable nursing intervention to increase adherence to self-care among patient with Diabetes Mellitus. Keywords: diabetes mellitus, adherence, self-care.